2022
DOI: 10.21203/rs.3.rs-1357296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TRIM24 controls induction of latent HIV-1 by stimulating transcriptional elongation

Abstract: Expression of HIV-1 in response to T cell signaling requires TFII-I bound to conserved sites flanking the LTR enhancer. Here we demonstrate that TFII-I recruits tripartite motif protein TRIM24 to the HIV-1 LTR by direct interaction. Constitutive interaction of TRIM24 with the LTR was dependent upon TFII-I, and knockout of TRIM24 impaired reactivation of HIV-1 expression in response to T cell signaling. Loss of TRIM24 did not affect recruitment of RNA Pol II to the LTR promoter, but inhibited transcriptional el… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(47 citation statements)
references
References 50 publications
13
34
0
Order By: Relevance
“…8D, RBE1). These results are consistent with our previous observations indicating that recruitment of TRIM24 to the HIV-1 LTR causes enhanced recruitment of pTEF-b/ Cdk9, which promotes RNAPII CTD S2 phosphorylation and elongation of transcription [18].…”
Section: Iacs-9571 Stimulates Hiv-1 Transcriptional Elongation Our Pr...supporting
confidence: 94%
See 4 more Smart Citations
“…8D, RBE1). These results are consistent with our previous observations indicating that recruitment of TRIM24 to the HIV-1 LTR causes enhanced recruitment of pTEF-b/ Cdk9, which promotes RNAPII CTD S2 phosphorylation and elongation of transcription [18].…”
Section: Iacs-9571 Stimulates Hiv-1 Transcriptional Elongation Our Pr...supporting
confidence: 94%
“…Consistent with our previous results indicating that TRIM24 is required for reactivation of latent HIV-1 [18] we found that cells treated with concentrations of dTRIM24 that reduce TRIM24 protein levels also displayed a corresponding decrease in expression of the 5' LTR dsRed reporter in these cells (Fig. 5C).…”
Section: Protac-induced Degradation Of Trim24 Inhibits Hiv-1 Expressionsupporting
confidence: 92%
See 3 more Smart Citations